2008
DOI: 10.1007/s11010-008-9921-3
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules

Abstract: Liver-specific ZP domain-containing protein (LZP) was recently identified as a secreted protein that is specifically expressed in liver. However, the physiological effects of LZP are largely unknown. In this study, we found that LZP was detectable in mouse kidneys, testes, ovaries and heart, in addition to liver. LZP was localized in the spermatid cells of testes, corpus luteum cells of ovaries, and cardiac muscle cells of heart. But the protein mainly anchored on the apical membrane of the thick ascending lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Relatively higher expression was detected in kidney tissue. Renal expression of ZP proteins has also been detected in rat, Rattus norvegicus and mouse, Mus musculus [56]. The expression of ZP2 was found to be two-to seven-fold higher in resistant line fish in our previous study [16], but in the present study no significant differential expression was detected.…”
Section: Differential Expression In Divergent Linescontrasting
confidence: 47%
“…Relatively higher expression was detected in kidney tissue. Renal expression of ZP proteins has also been detected in rat, Rattus norvegicus and mouse, Mus musculus [56]. The expression of ZP2 was found to be two-to seven-fold higher in resistant line fish in our previous study [16], but in the present study no significant differential expression was detected.…”
Section: Differential Expression In Divergent Linescontrasting
confidence: 47%
“…In our extending study, this gene was found to be expressed in mouse and rat kidney, where OIT3 was co‐localized with Tamm–Horsfall protein (THP) in the renal thick ascending limb of Henle's loop (TAL). The in vivo interaction between OIT3 and THP was further confirmed in kidney and urine by co‐immunoprecipitation assay, and the in vitro interaction was detected by GST pull‐down assay [5].…”
Section: Introductionmentioning
confidence: 78%
“…Intriguingly, salt appears to stimulate uromodulin to form filaments (Bokhove et al, 2016). Furthermore, the ZP protein Oit3 (also known as LZP), a proposed partner of uromodulin, can form spherical aggregates of unknown organization in vitro (Shen et al, 2009). However, how these Oit3 aggregates assemble, if they include other co-factors, such as uromodulin or salts, and whether they form in vivo is not clear.…”
Section: Zpc Domains Can Function Independently Of Zpn Domainsmentioning
confidence: 99%
“…Loss or dysfunction of these ZP proteins is associated with many human diseases, including chronic kidney disease, deafness, and hereditary hemorrhagic telangiectasia (HHT) (Cummings et al, 2018;Mapes et al, 2017;McAllister et al, 1994;Mustapha et al, 1999;Renner et al, 2007;Roggenbuck et al, 2009;Verhoeven et al, 1998;Wheeler & Thomas, 2019;Wong et al, 2000). Several ZP proteins are thought to act primarily by trapping ligands and affecting signaling processes (Lin, Hu, Zhu, Woodruff, & Jardetzky, 2011;Saito et al, 2017), but many form fibrils or aggregates that may play structural roles within the aECM (Bokhove & Jovine, 2018;Jovine et al, 2002;Porter & Tamm, 1955;Shen et al, 2009). How ZP proteins assemble into complex extracellular matrix structures in vivo is poorly understood.…”
Section: Introductionmentioning
confidence: 99%